Diltiazem is a useful and effective medication for reversal of coronary artery spasm-induced complete atrioventricular block: A case report - Zhang, Jin; Liu, Li; Liu, Chengwei; Han, Min; Xu, Chengyi; Qiu, Rujie (Frontiers in Cardiovascular Medicine, 2023)
Coronary artery spasm (CAS) is characterized by reversible diffuse or focal vasoconstriction, a phenomenon that plays an important role in the pathogenesis of ischemic heart disease. Fatal arrhythmias, such as ventricular tachycardia/fibrillation (VT/VF) and complete atrioventricular block (AV-B) are very common in patients with CAS. Non-dihydropyridine calcium channel blockers (CCB)such as diltiazem were recommended as first line medications for the treatment and prevention of CAS episodes. However, its use remained controversial in CAS patients with AV-B as this type of CCB can also cause AV-B itself. Here, we present the use of diltiazem in patient with III AV-B caused by CAS. The patient’s chest pain was rapidly relieved and complete AV-B was promptly restored to sinus rhythm following the administration of intravenous diltiazem without any adverse effects. In this report we highlight the useful and effective application of diltiazem for the treatment and prevention of III AV-B caused by CAS.